REVISITING THE NUCLEOPHILICITY CONCEPT IN A COMPREHENSIVE BIOMASS VALORIZATION EXPERIMENT: FROM PAPAYA SEEDS TO THIOUREA MOTIFS - Santos, Raquel; Viana, Gil; Moreira, Anderson; Nóbrega, Vitor; Silva, Vitor; Malta, Luiz Fernando; Aguiar, Lucia; Senra, Jaqueline (Química Nova, 2019)
The recovery of waste materials with potential for synthetic transformations is a major field in science. However, just few experiments have been devoted to undergraduate students by exploring some consistent subjects in light of simple, natural resources. Nucleophilicity is a central subject in chemistry and there are significant synthetic models to exploit it in contrast to basicity. Here we present a laboratory experiment that utilizes hands-on research to be implemented in an organic chemistry lab by using benzyl isothiocyanate (BITC) from papaya seeds as raw material for the preparation of thioureas in a fast and visually indicative experiment. Subjects such as green chemistry, extraction methods, nucleophilicity, chromatography and NMR spectroscopy can be emphasized in order to implement a project-based approach. This experiment shows flexibility concerning the procedures and the use of biomass raw materials towards the reinforcement of a research-like experience and critical-thinking skills.